Case Report: Prenatal Identification of a De Novo Mosaic Neocentric Marker Resulting in 13q31.1→qter Tetrasomy in a Mildly Affected Girl - Dharmadhikari, Avinash V.; Pereira, Elaine M.; Andrews, Carli C .; Macera, Michael; Harkavy, Nina; Wapner, Ronald; Jobanputra, Vaidehi; Levy, Brynn; Ganapathi, Mythily; Liao, Jun (Frontiers in Genetics, 2022)
Partial tetrasomy of distal 13q has a reported association with a variable phenotype including microphthalmia, ear abnormalities, hypotelorism, facial dysmorphisms, urogenital defects, pigmentation and skin defects, and severe learning difficulties. A wide range of mosaicism has been reported, which may, to some extent, account for the variable spectrum of observed phenotypes. We report here a pregnancy conceived using intrauterine insemination in a 32-year-old female with a history of infertility. Non-invasive prenatal screening (NIPS) was performed in the first trimester which reported an increased risk for trisomy 13. Follow-up cytogenetic workup using chorionic villus sampling (CVS) and amniotic fluid samples showed a mosaic karyotype with a small supernumerary marker chromosome (sSMC). Chromosomal microarray analysis (CMA) identified a mosaic 31.34 Mb terminal gain on chr13q31.1q34 showing the likely origin of the sSMC to distal chromosome 13q. Follow-up metaphase FISH testing suggested an inverted duplication rearrangement involving 13q31q34 in the marker chromosome and the presence of a neocentromere. At 21 months of age, the proband has a history of gross motor delay, hypotonia, left microphthalmia, strabismus, congenital anomaly of the right optic nerve, hemangiomas, and a tethered spinal cord. Postnatal chromosome analyses in buccal, peripheral blood, and spinal cord ligament tissues were consistent with the previous amniocentesis and CVS findings, and the degree of mosaicism varied from 25 to 80%. It is often challenging to pinpoint the chromosomal identity of sSMCs using banding cytogenetics. A combination of low-pass genome sequencing of cell-free DNA, chromosomal microarray, and FISH enabled the identification of the precise chromosomal rearrangement in this patient. This study adds to the growing list of clinically identified neocentric marker chromosomes and is the first described instance of partial tetrasomy 13q31q34 identified in a mosaic state prenatally. Since NIPS is now being routinely performed along with invasive testing for advanced maternal age, an increased prenatal detection rate for mosaic sSMCs in otherwise normal pregnancies is expected. Future studies investigating how neocentromeres mediate gene expression changes could help identify potential epigenetic targets as treatment options to rescue or reverse the phenotypes seen in patients with congenital neocentromeres.